[PS 01-23] SYNERGISTIC EFFECT OF A TISSUE KALLIKREIN 1 AND TISSUE INHIBITOR OF MATRIX METALLOPROTEINASE 1 CO—EXPRESSION VECTOR ON THE PROLIFERATION OF RAT VASCULAR SMOOTH MUSCLE CELLS. (September 2016) - Yu, Peng; Huang, Shujie; Yu, Huizhen; Xiang, Hong; Zhu, Pengli
Abstract : Objective: Tissue kallikrein 1 (TK1) and tissue inhibitor of matrix metalloproteinase 1 (TIMP1) are important in inhibiting vascular smooth muscle cell (VSMC) proliferation and improving vascular remodeling, respectively. It was hypothesized that a combination of TK1 and TIMP1 genes, mediated by an adenovirus vector could augment or act in synergy to enhance the inhibitory effects. Design and Method: The promoter, mCMV carrying hTIMP1 cDNA was subcloned into pDC316—hTK1 to construct a recombinant plasmid carrying hTK1 and hTIMP1 genes. Subsequently, the double gene plasmid and adenovirus backbone plasmid were packaged into HEK293A cells. Gene transcription and protein expression were examined, respectively using reverse transcription—quantitative polymerase chain reaction (PCR) and western blotting assays. VSMC proliferation was assessed using cell counting and methyl—thiazolyl—tetrazoliuin methods. Results: The constructed plasmid containing hTK1 and hTIMP1 genes was correctly identified by means of PCR, double digestion and sequencing analysis. The co—expression vector, Ad—hTK1—hTIMP1 was successfully constructed and packaged into HEK293A cells. When VSMCs were transfected with the co—expression vector, the mRNA transcription and protein expression of hTK1 and hTIMP1 exhibited abundant expression in a concentration—dependent and time—dependent manner, independently. Conclusions: The co—expression vector synergistically inhibited the cell growth and proliferation induced by platelet—derived growth factor—BB compared with the single gene vector.